2006
DOI: 10.1517/14656566.7.3.297
|View full text |Cite
|
Sign up to set email alerts
|

Fungal infections in solid organ transplantation

Abstract: Renal, liver, heart and lung transplantation are now considered to be the standard therapeutic interventions in patients with end-stage organ failure. Infectious complications following transplantation are relatively common due to the transplant recipients overall immunosuppressed status. The incidence of invasive mycoses following solid organ transplant ranges from 5 to 42% depending on the organ transplanted. These mycoses are associated with high overall mortality rates. Candida and Aspergillus spp. produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 78 publications
1
43
0
2
Order By: Relevance
“…Systemische Pilzinfektionen gehören zu den klassischen opportunistischen Erkrankungen bei transplantierten Personen, mit hohen Morbiditäts-und Letalitätsraten [23,24,26]. Die Inzidenz von Pilzinfektionen variiert je nach Quelle und transplantiertem Organ deutlich [16]. So liegt die Rate der systemischen Pilzinfektionen nach Lebertransplantationen mit 4-50% am höchsten, während sie für thorakale Transplantationen mit 15-35% und für Nierentransplantationen mit 2-14% angegeben wird [9].…”
Section: Grundlagenunclassified
“…Systemische Pilzinfektionen gehören zu den klassischen opportunistischen Erkrankungen bei transplantierten Personen, mit hohen Morbiditäts-und Letalitätsraten [23,24,26]. Die Inzidenz von Pilzinfektionen variiert je nach Quelle und transplantiertem Organ deutlich [16]. So liegt die Rate der systemischen Pilzinfektionen nach Lebertransplantationen mit 4-50% am höchsten, während sie für thorakale Transplantationen mit 15-35% und für Nierentransplantationen mit 2-14% angegeben wird [9].…”
Section: Grundlagenunclassified
“…to fluconazole for C. albicans . The limited data which are available for prophylactic and empirical treatment strategies of invasive fungal infections in solid organ transplant patients have been reviewed very recently by Marik [57]. …”
Section: Therapy Of Postoperative Bacterial/fungal Infectionsmentioning
confidence: 99%
“…The high occurrence of fungal infection could be explained by the immunocompromised status of posttransplant patients and also the angioinvasive nature of fungi. 7,8 Leonardou et al reported two cases with P. aeruginosa isolated from the blood culture, and both patients were treated with ciprofloxacin for 4 weeks in total after surgery. 4 No recurrence was detected up to 36 months.…”
mentioning
confidence: 99%